Portrait of Theodor Curtius, 1910 - Kögel, Max (1910)
Portrait of Theodor Curtius (1857-1928) taken at E. Schultze photography studio. Throughout his career, Curtius was a professor of chemistry at the University of Heidelberg, the director of the analytical chemistry department at the University of Erlangen, and a chair of chemistry at the University of Kiel. He defined the Curtius rearrangement in 1890 and discovered diazoacetic acid, hydrazine, and hydrazoic acid later in his career.
Keywords: Curtius, Theodor, 1857-1928; Universität Heidelberg; Chemists; College teachers; Carte de visite photographs